Strategi Lembaga Kursus Dan Pelatihan (LKP) Komputer Algerian Dalam Mengembangkan Life Skill Masyarakat - Husna Umaira; Suryati Suryati; Irpinsyah Irpinsyah (Social Science and Contemporary Issues Journal, 2023)
This research investigates the strategies implemented by LKP Komputer Algerian in efforts to develop life skillss within the community. Life skillss play a crucial role in equipping individuals with the necessary abilities to face various challenges in their daily lives. LKP Komputer Algerian, as a non-formal education institution, holds a strategic role in providing life skillss training to the community. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observations, and analysis of relevant documents. The main respondents involved administrators, instructors, and participants in the training programs at LKP Komputer Algerian. The results of the research indicate that LKP Komputer Algerian implements several effective strategies in developing life skillss within the community. These strategies involve interactive learning methods, the utilization of information technology, the development of relevant curricula, and active participation of participants in practical activities. Additionally, LKP Komputer Algerian collaborates with relevant stakeholders to expand the reach and impact of their life skillss training programs. This research is expected to provide a better understanding of successful practices carried out by LKP Komputer Algerian in the context of life skillss development. The implications of these findings can serve as a guide for similar institutions and other stakeholders in efforts to enhance the life skillss of the community through non-formal education approaches.